2015
DOI: 10.3109/09553002.2015.1028598
|View full text |Cite
|
Sign up to set email alerts
|

Health, growth and reproductive success of mice exposed to environmentally relevant levels of Ra-226 via drinking water over multiple generations

Abstract: Based on the endpoints measured on four generations of mice, there is no indication that the consumption of radium-226 via drinking water (at activity concentrations up to 8.0 Bq/l) affects health, growth and reproductive fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Experiments using 18 generations of exposed mice with the daily dose about 0.29 mGy suggested that low-dose low-rate exposures do not affect the sex ratio in mouse litters [43]. No radiation-induced sex ratio changes in the offspring of mice were found by other researchers [44][45][46][47][48]. Note that doses applied in animal experiments are much higher than average doses to the residents of contaminated territories after the Chernobyl accident.…”
Section: Issn: 2471-4879mentioning
confidence: 89%
“…Experiments using 18 generations of exposed mice with the daily dose about 0.29 mGy suggested that low-dose low-rate exposures do not affect the sex ratio in mouse litters [43]. No radiation-induced sex ratio changes in the offspring of mice were found by other researchers [44][45][46][47][48]. Note that doses applied in animal experiments are much higher than average doses to the residents of contaminated territories after the Chernobyl accident.…”
Section: Issn: 2471-4879mentioning
confidence: 89%
“…Experiments using 18 generations of exposed mice with the daily dose ∼0.29 mGy suggested that low-dose low-rate exposures do not affect the sex ratio in mouse litters [14]. No radiation-induced sex ratio changes in the offspring of mice were found by other researchers [15][16][17][18][19]. On the contrary, a study and review from the year 1968 concluded that there is a sex ratio shift following spermatogonial exposure in rats [20].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments using 18 generations of exposed mice with the daily dose ∼0.29 mGy suggested that low-dose low-rate exposures do not affect the sex ratio in mouse litters [10]. No radiation-induced sex ratio changes in the offspring of mice were found by other researchers [11][12][13][14][15]. On the contrary, a study and review from 1968 concluded that there is a sex ratio shift following spermatogonial exposure in rats [16].…”
mentioning
confidence: 99%